2017
DOI: 10.1186/s12711-017-0354-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of selection sweeps identified between fine-wool Merino and coarse-wool Churra sheep breeds

Abstract: BackgroundWith the aim of identifying selection signals in three Merino sheep lines that are highly specialized for fine wool production (Australian Industry Merino, Australian Merino and Australian Poll Merino) and considering that these lines have been subjected to selection not only for wool traits but also for growth and carcass traits and parasite resistance, we contrasted the OvineSNP50 BeadChip (50 K-chip) pooled genotypes of these Merino lines with the genotypes of a coarse-wool breed, phylogenetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 112 publications
4
27
0
Order By: Relevance
“…Similar findings were also reported in Italian sheep breeds [22], Spanish sheep breeds [21], Swiss sheep breeds, and Merino [18,31]. Moreover, the selective signatures in NCAPG/LCORL region were found in many sheep breeds [18,32,33], including Merino [34]. A previous genome-wide association study (GWAS) demonstrated that this region was associated with body weight in Australian Merino [35].…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings were also reported in Italian sheep breeds [22], Spanish sheep breeds [21], Swiss sheep breeds, and Merino [18,31]. Moreover, the selective signatures in NCAPG/LCORL region were found in many sheep breeds [18,32,33], including Merino [34]. A previous genome-wide association study (GWAS) demonstrated that this region was associated with body weight in Australian Merino [35].…”
Section: Discussionsupporting
confidence: 81%
“…One important issue regarding the variant calling analyses reported here is that all the WGR datasets, those obtained from the public SRA repository and those generated by our research group, were processed following the same bioinformatic analysis workflow and were considered jointly for the variant calling analysis. This procedure has been used in previous studies analyzing WGR datasets [ 35 , 43 , 44 ] and has been proven to prevent biased results regarding the variant calling detection process.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed WGR datasets of 43 The variant calling analyses performed across the whole genome revealed, after quality filters, a total of 81,053,638 variants across the entire genome, 59.98% of which had been previously described in the database provided by Ensembl (dbSNP release 91). After filtering the regions corresponding to the 24 functional candidate genes considered here, the total number of variants to be further assessed was 20,100, most of which were SNPs (17,037 and 16,960, for SnpEff and VEP, respectively), with lower numbers of insertions (1489 and 1245, for SnpEff and VEP, respectively) and deletions (1574 and 1396, SnpEff and VEP, respectively) (see details in Table 1).…”
Section: Genetic Variability and Phylogenetic Relationship Between Samentioning
confidence: 99%
“…We propose that this phenotypic differentiation reflects the opposing and varying effects of human selection for fine wool production and environmental adaptation favoring the more natural coarse wool. As for the tail traits, wool quality is controlled by a restricted number of genes [59,73,74].…”
Section: The Origin Of European Sheepmentioning
confidence: 99%